The burden of insomnia among public health sector nurses in KwaZulu-Natal, South Africa - Phatheka P. Ntaba; Sibongile Mashaphu; Kalpesh Narsi (South African Journal of Psychiatry)
Background: Insomnia is defined as poor quantity or quality of sleep resulting in impaired daytime functioning and distress. Insomnia has been found to occur at higher rates in health care workers and has been associated with physiological dysfunction, illness and distress as well as many socio-demographic and lifestyle-related factors.